A Comparison of American, Norwegian, and Russian Standards in Calculating the Wall Thickness of Submarine Gas Pipeline - Dianita, Cindy; Dmitrieva, Tatyana Vladimirovna (UI Scholars Hub, 2016)
One of the key issues in the pipeline design is wall thickness calculation. This paper highlights a comparison of wall thickness calculation methods of submarine gas pipeline based on Norwegian Standard (DNV-OS-F101), Indonesian Standard SNI 3474 which refers to American Standard (ASME B31.8), and Russian Standard (VN39-1.9-005-98). A calculation of wall thickness for a submarine gas pipeline in Indonesia (pressure 12 MPa, external diameter 668 mm) gives the results of 18.2 mm (VN39-1.9-005-98), 16 mm (ASME B31.8), and 13.5 mm (DNV-OS-F101).The design formula of hoop stress due to internal pressure is interpreted in different ways for every standard. Only Norwegian Standard requires calculating hoop stresses in the inner surface, which leads to a decreased value of the wall thickness. Furthermore, the calculation of collapse factor due to external pressure is only regulated in American and Norwegian Standards while Russian Standard uses that factor as an intermediate parameter in calculating local buckling. For propagation buckling, either Russian or American Standard explains empirical formula of critical hydrostatics pressure as the input in propagation buckling calculation. This formula is almost similar to the empirical formula of Norwegian Standard. From the comparison of these standards, DNV OS-F101 gives more stringent requirements than others.